Isolation, selection and identification of bacterial strain BHN2 producing bacterial cellulose - Lam, Duong Minh; Thuy Van, Nguyen Thi; Kim Nhung, Dinh Thi (Academia Journal of Biology, 2013)
Bacterial cellulose membrane has been applied in both industrial and routine life. This is the first research on molecular identification of cellulose producing bacteria in Vientam. In this paper, we selected the bacterial strain BHN2, which was capable to produce bacterial cellulose, from 12 strains isolated from Hanoi fresh beer. The strain BHN2 produced the bacterial cellulose characterized by thin, smooth, uniform and high water absorption that could be suibtable to use in curing burnt injuries. The most suitable medium used for producing membrane consists of the following ingridients (NH4)2SO4: 3 g, KH2PO4: 2 g, MgSO4.7H2O: 2 g, coconut milk 1,000 ml. The result of 16S rDNA sequence analysis indicated that the strain BHN2 belongs to Gluconacetobacter intermedius. This strain has a high potential application in producing cellulose membrane, that used in curing burnt injuries.